Tuning proportional integral controller to enhance the photovoltaic system performance - Nadhim, Rasha Fahim; Ibrahim, Anmar Khalil (Bulletin of Electrical Engineering and Informatics, 2023)
This paper presented a closed loop buck-boost converter controlled by using proportional and integral controller (PIC) for photovoltaic (PV) applications. The mathematical equations of design the solar panel type KC200GT and buck–boost converter is illustrated. The electrical behaviors of solar panel are examined at 1,000 light radiation and room temperature (25 °C) situation. A PIC tuning is difficult with conventional methods such as graphs and mathematical analysis, so for that reason two approaches are used for tuning and optimization of PIC, particle swarm optimization (PSO), and Zeigler–Nichols (ZN). The suggested closed loop application through the converter preserves the constant voltage in the output spite of alterations to the input voltage, decreases settling time, overshoot and ripple voltage to minimum value that enhancement the efficiency of the converter. The results show that the PSO approach is improved than the ZN approach. The proposed model is constructed by using SimPower system tool box in MATLAB package.